2020
DOI: 10.1108/jhlscm-03-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Cross-evaluation based super efficiency DEA approach to designing disaster recovery center location-allocation-routing network schemes

Abstract: PurposeFinding efficient disaster recovery center location-allocation-routing (DRCLAR) network schemes play a vital role in the disaster recovery logistics network (DRLN) design. The purpose of this paper is to propose and demonstrate how to design efficient DRCLAR network schemes under the risk of facility disruptions as a part of the disaster relief activities.Design/methodology/approachA goal programming (GP) model is formulated to consider four performance measures simultaneously for the DRCLAR design. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Based on the influence of Fujian Jinsen enterprise's aggregate efficiency value in 2019, we reranked the enterprises' scores using the super-efficiency DEA model to determine effective DMUs in 2019. Thus, scores with a total efficiency value above criterion 1 are recommended [122,124,125]. The outcome demonstrated that most high-performance companies achieved an efficiency value above criterion value one after the re-ranking [122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the influence of Fujian Jinsen enterprise's aggregate efficiency value in 2019, we reranked the enterprises' scores using the super-efficiency DEA model to determine effective DMUs in 2019. Thus, scores with a total efficiency value above criterion 1 are recommended [122,124,125]. The outcome demonstrated that most high-performance companies achieved an efficiency value above criterion value one after the re-ranking [122].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that most high-performance companies attained an efficiency value above criterion value one after re-ranking [122] Table 3 shows the performance efficiency values of forestry listed companies obtained in 2019 based on the super-efficiency DEA model. Stemming from the impact of Fujian Jinsen company's overall comprehensive efficiency average value in 2019, this study reranked the super-efficiency DEA for the listed forestry companies in 2019 to determine the DMUs with a total efficiency value above the criterion value 1 [122,124,125]. The results indicated that most high-performance companies attained an efficiency value above criterion value one after re-ranking [122].…”
Section: Super-efficiency Dea Static Efficiency Evaluationmentioning
confidence: 99%
“…With respect to studies on the VRP optimization model and algorithm solution in emergency logistics, some researchers have focused on the location-allocation problem (LAP) [18][19][20] and relief distribution scheduling problem [21,22] in emergency logistics system optimization. Some researchers have discussed VRP in an emergency from different perspectives and designed corresponding accurate algorithms and heuristic algorithms.…”
Section: State Of the Artmentioning
confidence: 99%
“…Bozorgi-Amiri et al [49] proposed a compromise pro-gramming model to provide managerial insights about facility location and allocation in disaster relief systems. Fang and Li [50] and Hong and Jeong [51] combined specific location modeling goal with the DEA model to address a facility location-allocation (FLA) problem.…”
Section: Location-allocation Problem For Relief Center/humanitarian L...mentioning
confidence: 99%